Alternative institutional arrangements towards optimal water allocation - Gakpo, Emmanuel Foster Yao (University of the Free State, 2002)
The limited natural availability of water resources in South Africa coupled with the increasing competition between water users demands that, reallocation and sustainable use of water be given serious attention. Bringing into perspective factors leading to the vulnerability of water resources, focus is placed on institutional issues, which is becoming a thorny issue nationally. Drawing on institutional economic theory a generic water institutional framework is developed to assist in shaping institutional arrangements towards achieving economic and social objectives simultaneously, in order to guarantee water security. In this thesis an ideal institutional framework was developed and used in conjunction with global trends and patterns in water policy and institutional arrangements, to evaluate the South African water law and water policy. The evaluation revealed that factors like: excessive government control of water management institutions; bureaucratic consented water reallocations; administratively set pricing mechanisms; lack of appropriate arrangements to facilitate tradable entitlements (like defining exclusive rights to entitlements); unclear water transfer arrangements; and lack of definitive institutional provisions for integrated demand and supply management, deviate from current international water institutional trends and also fall short of an ideal institutional arrangement that will lead to water security. The weaknesses in the current South African water laws and policies prompted the search for alternative institutional arrangements, which particularly have the potential to offer more opportunities for effective water allocation and management, and largely based on decentralisation and full stakeholder participation. A number of alternatives were studied and Capacity Sharing (CS) was identified as the most appropriate. Capacity sharing is an institutional arrangement with property rights structured to allocate water among multiple users of water resource systems. This form of institutional arrangement provides each user or group of users of reservoir water with perpetual or long-term rights to a percentage of reservoir inflows and a percentage of reservoir storage capacity. Capacity Sharing has the capacity to solve the potential South African water scarcity problem, because of its dependence on water markets, as well as its decentralised tendency. In addition, the attributes of flexibility, predictability and security of tenure, rank CS as one of the best alternative institutional arrangements. However, critical issues like: water rights; water transfers; water markets; and the general administrative control, need some minor institutional amendments if CS is to be adopted in South Africa. A case study at Vanderkloof dam assumes the existence of CS in which the arrangement provides Ramah Canal irrigation water users exclusive right to allotted reservoir capacity shares as well as inflow shares, in an effort to test the applicability of CS, as well as the benefits it can offer the water user. A simulation model SIM-DY-SIM was used to determine Marginal Value Products (MVPs) for 75-hectare farm, under two Crop Mix scenarios of cultivating lucern, maize and wheat; potatoes, maize and wheat. The results show that, MVPs (which determine the farmer's ability to pay for water) differ significantly with respect to crop mixes and also across seasons. The shadow prices (MVPs) were also derived at different water scarcity scenarios to determine the optimal water use policies that the farmer would pursue. The MVPs, indicating the ability to pay in the immediate season or in the future, provide the capacity for determining water prices in both the present and in the future. This characteristic is very vital for trading water rights. The MVPs also facilitate good water use decision-making since they are linked to the decision to release or save water. The implications of these MVP values for water transfers and trading and hence allocation and efficient use of water becomes apparent. The other set of results compared the use of SDP derived rules with the alternative of no rules pertaining to the farmer's water supply reliability. It is noted that reservoir capacity and inflow shares, which ultimately determine the farmer's water supply reliability, were better-managed using SDP derived rules than without rules. Deductions from the SDP simulations from the viewpoint of the usefulness of MVPs to value water, to the advantages of using SDP derived rules to make optimal water use decisions, opens a new frontier for efficient allocation and use of South Africa's water resources.
Dissertation (M.Sc. Agric. (Agricultural Economics))--University of the Free State, 2002
Keywords: Water-supply -- South Africa; Water transfer -- South Africa; Water use -- South Africa